The Influence of Organizational Culture on Inpatient Staff Performance of QIM Hospital - Atmojo, Agung; Purnomo, Imam Purnomo; Muljono, Slamet (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
ABSTRACT                                                     Organizational culture plays an important role in stimulating the human resources work spirit. The organizational environment affects staff behavior and appearance, as well as staff performance. QIM Hospital is a new hospital. Therefore, it is needed to know the influence of organizational culture on staff performance in the inpatient staffs of QIM Batang Hospital. Using a quantitative research with the survey method. The population in this research was all in-patient staffs of QIM Batang Hospital. A 51 people as a sample and choosen using simple random sampling. Data taken with questionnaire instrument, then analyzed using simple linear regression. The results showed that organizational culture has a positive and significant effect on staff performance. The influence of organizational culture on staff performance is 64.4% (the coefficient of determination of 0.644).   ABSTRAK   Budaya organisasi berperan penting dalam  merangsang semangat kerja sumber daya manusia. Lingkungan organisasi mempengaruhi perilaku dan penampilan pegawai serta kinerja pegawai. RS QIM merupakan rumah sakit yang tergolong baru. Sehingga perlu diketahui pengaruh budaya organisasi terhadap kinerja pegawai rawat inap Rumah Sakit QIM Batang. Melalui penelitian kuantitatif menggunakan metode survei. Populasi dalam penelitian ini adalah seluruh pegawai rawat inap Rumah Sakit QIM Batang. Sampel sebanyak 51 orang menggunakan simple random sampling, instrumen kuesioner, dan data dianalisis menggunakan regresi linier sederhana. Hasil menunjukkan bahwa budaya organisasi memiliki pengaruh positif dan signifikan terhadap kinerja pegawai. Pengaruh budaya organisasi terhadap kinerja pegawai sebesar 64,4% (koefisien determinasi sebesar 0,644).